Immediate Loading Of Basal Implants In Patients With Compromised Bone Quality A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Immediate loading of dental implants has gained increasing attention as a means of reducing treatment time and improving patient satisfaction. In patients with compromised bone quality, however, conventional endosseous implants often require bone augmentation procedures and prolonged healing periods. Basal implants, which engage cortical bone and achieve high primary stability, have emerged as an alternative that allows immediate functional loading even in severely resorbed or poor-quality bone.Objective: This systematic review aimed to critically evaluate recent clinical evidence (2020–2025) on the outcomes of immediately loaded basal implants in patients with compromised bone quality, focusing on implant survival, success rates, biological and mechanical complications, and patient-reported outcomes.Materials and Methods: A systematic literature search was conducted following PRISMA guidelines using PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar. Studies published between January 2020 and December 2025 were screened. Inclusion criteria comprised clinical studies reporting immediate loading of basal or corticobasal implants in patients with compromised bone quality. Data extraction and qualitative synthesis were performed.Results: Eleven studies (prospective studies, retrospective analyses, and case series) involving more than 1,200 basal implants were included. Reported survival rates ranged from 94.5% to 100% over follow-up periods of 6 months to 5 years. Immediate loading protocols demonstrated favorable functional and esthetic outcomes with low complication rates. Most failures occurred within the early healing phase and were associated with improper case selection or occlusal overload.Conclusion: Based on recent evidence, immediate loading of basal implants appears to be a predictable and effective treatment option for patients with compromised bone quality. However, the heterogeneity of study designs and limited randomized controlled trials highlight the need for further high-quality research.